Continuous negative extrathoracic pressure and bronchiolitis - Yanney, Michael Peter (2008)
Bronchiolitis is the commonest cause of acute respiratory failure in infancy and several hundred children need respiratory support for the condition each year in the United Kingdom. Continuous negative extrathoracic pressure (CNEP) has been used to support such children but concerns about its possible association with significant harm prompted a government enquiry into the conduct of research at a UK centre using the technique. This retrospective study was designed to address these concerns by careful evaluation of outcome in two matched cohorts. Fifty children who had received CNEP for bronchiolitis as infants were compared with 50 controls who were treated in another hospital during the same period. Pre-treatment variables, demographics and neonatal factors were well matched in the two groups. In all subjects questionnaires and clinical examination were used to assess respiratory symptoms, disability and health-related quality of life whilst respiratory function was assessed by measuring airway resistance using the interrupter technique (Rint), by spirometry and by bronchodilator responsiveness. CNEP was associated with reduced need for, and shorter duration of, positive pressure ventilation but with longer periods in oxygen and hospital. Median Rint was 16.5% higher in the CNEP cohort (p<0.001) and median FEF25-75 was 9.3% lower (p=0.029). There were no significant differences between the groups in FEV1, FVC, bronchodilator responses or respiratory symptoms, or in the prevalence of moderate or severe disability (Mantel-Haenszel statistic 1.40, 95% confidence intervals: 0.64 -3.04, p=0.39). Median health utility indices were similar; CNEP 1.00 (interquartile range: 0.85-1.00), controls 0.99 (interquartile range: 0.81 -1.00), n=48 pairs, p= 0.37. The higher Rint and lower FEF25-75 in the CNEP group represent a small difference in respiratory function that may be attributable to population differences but a CNEP effect cannot be excluded. Further evaluation of the use of CNEP in bronchiolitis requires a prospective, controlled study.